P2.43 Gender differences in risk factors and clinical outcomes of patients receiving antiretroviral therapy at an hiv clinic in guatemala city over a 9-year period. (8th July 2017) - Tharakan, Theresa; Anderson, Matt
Abstract : Introduction: There is no consensus on gender differences in clinical outcomes of HIV-infected patients. Immunologic, virologic, and survival data for patients receiving antiretroviral therapy (ART) show an inconsistent presence and direction of a gender gap. Gender and sexual behavior-based outcomes analysis is lacking in Guatemala, which has largely sexual transmission of HIV. We examine outcomes of HIV-positive Guatemalans receiving ART over a 9 year period. Methods: Retrospective cohort analysis was conducted using a database of treatment-naïve patients offered free ART at the Clinica Familiar Luis Angel Garcia in Guatemala City from 2004 to 2014. Multivariate Cox regression was used to study gender differences in all-cause mortality, immunologic failure (CD4 <100 cells/µL twice or CD4 < baseline) and virologic suppression (viral load <50 HIV-1 RNA copies/mL within 1 year of starting ART). Results: 4248 patients were included: 2605 men, 1617 women, and 26 transgender patients (analysed separately). Compared to men, women had higher median CD4 counts (198 vs. 126 cells/µL, p<0.001) and lower median viral loads (6.48 × 10 4 copies/mL vs. 11.27 × 10 4 copies/mL, p<0.001) at baseline. In multivariate analysis, mortality decreased with female gender (HR 0.52, 95% CI 0.29–0.93, p=0.029) while it increased with age (HR 1.02, 95% CI 1.003–1.04, p=0.02) and inconsistent condom use (HR 9.36, 95% CI 2.61–33.63, p=0.001). In women alone, these factors did not predict mortality. In men alone, mortality increased with inconsistent condom use (HR 23.26, 95% CI 2.89–187.3, p=0.003), and number of sexual partners (HR 1.02, 95% CI 1.001–1.039, p=0.041). Gender did not predict immunologic failure. Female gender predicted a lower rate of viral suppression (HR 0.6, 95% CI 0.41–0.85, p=0.005). Conclusion: Women receiving ART have lower mortality than men when adjusted for sociodemographic factors and sexual behaviours. Sexual risk factors affect genders differently and can predict treatment outcomes in previously infected patients.